(untitled) - Patton, Alec (London, 2012)
This guide is for teachers. It explains how to design and run projects for students that begin with an equiry and end with a tangible, publicly exhibited product.
Dạy học Tiếng Anh qua nhiệm vụ và dự án
Keywords: Phương pháp dự án trong dạy học,Học tập tích cực,Project method in teaching,Active learning